EU ENVIRONMENTAL LEGISLATION: MITIGATION OF DIRECTIVE ILLOCUTIONARY FORCE - Valentyna Snitsar (Філологічні студії, 2023)
This article discusses the illocutionary underpinning of varying degrees of legal force of an international document, derived from the conflict between its genre and institutional nature as an act of hard law and the sphere of environmental relations associated with soft law. The purpose of the article is to identify the types of hedging and mitigation of directive speech acts in the text of binding international law, and their impact on the degree of legal force of the document. Despite the predominance of directive speech acts that correspond to the obligative deontic modality of the document in accordance with the genre and institutional strategy of mandatory prescriptions, most of the acts are presented in indirect, hedged and mitigated versions with varying degrees of deintensification of the directive illocutionary force. The mitigation of coercion contributes to the discursive strategy of consensus and solidarity in such a sensitive area of international law as environmental legislation. The study revealed that the weakening of the intensity of directive illocutionary force is achieved by employing a number of mitigating and structural devices. The unconditional validity of legal force is reduced through hedging of explicit directives by introducing the parenthetical constructions in the propositional part of the act to refer to the circumstances, i.e. to the varying interests and needs of the states that can be taken into account during the implementation of the document. In addition to hedging, mitigation of explicit directive acts is achieved through bushes – the lexemes with the semes denoting an intention to act or a deliberation process instead of actions themselves that blur the propositional or denotative scope of statements, thus influencing the categoricity of the legal norm and, indirectly, its level of obligatoriness. The next type of directive action modifications affecting the mitigation of the directive illocutionary force is achieved through structural transformations of the directive act, whereby the designation of the states as subjects of the directive action is omitted and the position of the phrasal subject is occupied by the nomination of an object or a prescription purpose in combination with a binding verb. As a result, the utterance loses its performative-illocutionary part, which significantly affects the decrease in the degree of strength of the directive illocutionary force.